2008
DOI: 10.3174/ajnr.a1135
|View full text |Cite
|
Sign up to set email alerts
|

Giant Extracranial Aneurysms of Both Internal Carotid Arteries with Aberrant Jugular Veins in a Patient with Neurofibromatosis Type 1

Abstract: SUMMARY:Although neurofibromatosis type 1 (NF-1) is commonly considered neurocutaneous, severe arterial and venous abnormalities have been noted. Our patient, a 28-year-old woman, had bilateral giant extracranial aneurysms of the internal carotid arteries as well as skull base meningoceles involving the jugular foramina and aberrant jugular veins. CT and MR imaging, as well as digital subtraction and/or other angiography techniques, may be required to clarify pathology in patients with suggested vascular lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Our patient showed only aneurysmal lesions without definite stenotic lesion. Ku et al (5) reported a case of 28-year-old woman, had bilateral giant extracranial aneurysms of the internal carotid arteries, which shows very similar manifestation of cerebral vasculopathy in NF-1 to our patient. In comparison with our case of relatively asymptomatic 17-year-old boy, the patient developed sudden-onset symptoms related to her vascular lesions followed by prompt coil embolization and graft stent placement of the affected arteries.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our patient showed only aneurysmal lesions without definite stenotic lesion. Ku et al (5) reported a case of 28-year-old woman, had bilateral giant extracranial aneurysms of the internal carotid arteries, which shows very similar manifestation of cerebral vasculopathy in NF-1 to our patient. In comparison with our case of relatively asymptomatic 17-year-old boy, the patient developed sudden-onset symptoms related to her vascular lesions followed by prompt coil embolization and graft stent placement of the affected arteries.…”
Section: Discussionsupporting
confidence: 81%
“…Recent research on the morbidity and mortality in NF-1 disclosed 2 factors independently associated with an excess of mortality in children and adults under 30 years of age, soft tissue malignancies and vascular disease (5). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include compression or infiltration of adjacent blood vessels by a neurofibroma, anomalous vessels within a neurofibroma, spindle cell proliferation, and proliferation of nerves within blood vessel walls. 1,4 In the case herein described, histologic examination revealed a neurofibroma adjacent to the carotid artery aneurysm, which likely represent soft tissue involvement rather than the primary cause of the aneurysm. One theory is that the vascular lesions may result from a decrease in the protein product of NF-1 gene, neurofibromin, which shares sequence with the ras oncogene, leading to excessive endothelial and smooth muscle cells proliferation, a process analogous to that which produces the cutaneous neurofibromas.…”
Section: Discussionmentioning
confidence: 89%
“…Several case reports describe the link between stroke in NF1 patients with moyamoya syndrome [20][21][22] and other cerebral arteriopathies. 6,12,14,[23][24][25] Also, at least 1 case report describes a hypertensive stroke in a child with NF1. 26 However, to the best of our knowledge, there have been no population-based studies that address the risk of cerebrovascular events requiring hospitalization among patients with NF1.…”
mentioning
confidence: 99%